Total root remodelling by the Sleeve technique for aortic regurgitation in patients with repaired tetralogy of Fallot. (5th May 2019) - Eishi, Junichiro; Miura, Takashi; Obase, Kikuko; Eishi, Kiyoyuki
Abstract: We report the case of a 15-year-old male patient who had developed aortic regurgitation primarily because of aortic annulus dilatation late after definitive repair of tetralogy of Fallot. Valsalva sinus dilatation was not remarkable enough for root replacement. For the purpose of total root remodelling, the Sleeve procedure was employed. This procedure not only reduced the root diameters but also augmented commissure heights. With concomitant non-coronary cusp plication, aortic regurgitation was effectively controlled. Thus, the Sleeve technique may be a preferable option for patients who develop aortic regurgitation, due to dilatation of the annulus or sinotubular junction without significant dilatation of the sinus of Valsalva, after congenital heart surgery.